2021
DOI: 10.1016/s2589-7500(21)00116-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis detection from chest x-rays for triaging in a high tuberculosis-burden setting: an evaluation of five artificial intelligence algorithms

Abstract: Background Artificial intelligence (AI) algorithms can be trained to recognise tuberculosis-related abnormalities on chest radiographs. Various AI algorithms are available commercially, yet there is little impartial evidence on how their performance compares with each other and with radiologists. We aimed to evaluate five commercial AI algorithms for triaging tuberculosis using a large dataset that had not previously been used to train any AI algorithms.Methods Individuals aged 15 years or older presenting or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(172 citation statements)
references
References 19 publications
(29 reference statements)
9
123
3
1
Order By: Relevance
“…This is also the first time six of these CAD solutions have been independently evaluated in the literature. Previous systematic reviews have focused solely on Delft Imaging’s CAD4TB 24 , 25 , and more recent comparative evaluations 26 , 27 , 29 have included only a limited number of CAD solutions. This independent evaluation highlights the recent significant advances in diagnostic accuracy of multiple CAD software platforms and also identifies important limitations of the CAD software, which should be addressed in future implementation research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is also the first time six of these CAD solutions have been independently evaluated in the literature. Previous systematic reviews have focused solely on Delft Imaging’s CAD4TB 24 , 25 , and more recent comparative evaluations 26 , 27 , 29 have included only a limited number of CAD solutions. This independent evaluation highlights the recent significant advances in diagnostic accuracy of multiple CAD software platforms and also identifies important limitations of the CAD software, which should be addressed in future implementation research.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this CAD software evaluation was the involvement of two TB clinicians with different levels of experience as benchmarks for the software solutions. This particularly pertains to the inclusion of the Intermediate Reader, as many CAD software evaluations have used a single highly skilled radiologist to re-read the CXR images, thereby setting a very high standard for CAD software diagnostic accuracy 23 , 27 , 29 . However, experienced expert TB clinicians and radiologists are unlikely to participate in programmatic CXR screening initiatives on a regular basis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PPV of chest radiography for active TB among presumptive patients with a history of TB treatment in this study (21%) was lower than was previously found in Lusaka, Zambia among presumptive TB patients regardless of TB treatment history (33%) using chest radiography with computer-aided detection software [ 21 ]. In general, the performance of chest radiography as a screening and triage tool for TB disease according to prior TB treatment status is poorly characterized; however, a recent study from Bangladesh demonstrated that chest radiography using several different computer-aided detection software had substantially reduced diagnostic performance for active TB among those previously treated for TB [ 22 ]. Thus, it is important that future studies evaluate the accuracy of chest radiography and other TB screening and triage tools suitable for use in resource-limited settings (e.g., screening algorithms, prediction models, point-of-care tests), according to prior TB treatment status, to define optimal diagnostic strategies for this important patient population.…”
Section: Discussionmentioning
confidence: 99%